Central diabetes insipidus secondary to neurocysticercosis in a pediatric patient: A rare clinical intersection - Anil, Abhinav; Das , Surabhi; Kumar , Anil (Indian Journal of Case Reports, 2026)
Neurocysticercosis (NCC), caused by the larval stage of Taenia solium, is a leading cause of acquired epilepsy in endemic regions. While neurological symptoms predominate, endocrine manifestations such as central diabetes insipidus (DI) are exceedingly rare. We report a unique case of a 12-year-old male who presented to the emergency department with a 5-day history of profound polyuria and polydipsia. Evaluation confirmed central DI via a desmopressin challenge. Neuroimaging revealed a solitary ring-enhancing lesion in the left high parietal lobe, without direct hypothalamic pituitary involvement. The patient responded rapidly to a regimen of albendazole, corticosteroids, and desmopressin. This case highlights the potential for NCC to cause distal inflammatory disruption of the pituitary stalk, necessitating clinical suspicion for atypical metabolic presentations in endemic areas.